The Curriculum Design of Imam As-Shafi'i's Education and Its Relevance to the Indonesian Education System - Pahrurroji, Pahrurroji (Khazanah Pendidikan Islam, 2025)
In facing the dynamics of contemporary Islamic education, it is necessary to conduct studies that examine curriculum models based on traditional values that can adapt to the evolving times. This study examines the curriculum design of Imam As-Shafi'i and its relevance to Islamic education in Indonesia, particularly competency-based learning systems oriented toward character strengthening and knowledge integration. Using a qualitative approach through a literature study, this research conducts a descriptive- analytical examination of the educational curriculum structure of Imam As- Shafi'i and how its core values can be adapted to modern Islamic education systems. The findings show that Imam As-Shafi'i's educational curriculum emphasizes a balanced integration of Sharia knowledge, rational thought, and character formation based on dialogical learning that enhances students' critical and analytical thinking skills. Additionally, the curriculum developed by Imam As-Shafi'i highlights the importance of the ijtihad methodology in understanding religious texts, providing flexibility in its application across different historical and contextual settings. Furthermore, Imam As-Shafi'i's curriculum approach to learning ultimately encourages active interaction between teachers and students through discussion methods and argumentation based on textual evidence. This model not only shapes students with high analytical abilities but also encourages them to think independently in understanding and applying knowledge. This competency- based educational curriculum aligns with the needs of modern education systems, which emphasize problem-solving skills and adaptability to social and technological changes.